2013
DOI: 10.1136/bmjopen-2013-003062
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes following maternal exposure to second-generation antipsychotics given with other psychotropic drugs: a cohort study

Abstract: ObjectivesSecond-generation antipsychotics (SGAs), in conjunction with other psychotropic medications, are increasingly used to treat psychiatric disorders in pregnancy. The few available studies investigating the reproductive safety of SGAs did not reach conclusive results, and none have compared monotherapy with polytherapy involving other psychotropic medications.DesignDescriptive cohort study using a prospectively collected database.SettingMotherisk Program, The Hospital for Sick Children, Toronto, Canada.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
123
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(135 citation statements)
references
References 49 publications
5
123
3
4
Order By: Relevance
“…Extrapyramidal and withdrawal symptoms have been described in neonates following late pregnancy exposure to antipsychotic medication (Gentile, 2010;Habermann et al, 2013;Sadowski et al, 2013 effects-or-withdrawal-symptoms-in-newborns) have issued relevant safety labelling, and recommended relevant monitoring for neonates. However, studies that adequately controlled for confounding did not find a specific association between antipsychotic exposure and poor neonatal adaptation (Petersen et al, 2016;Vigod et al, 2015).…”
Section: Neonatal and Developmental Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapyramidal and withdrawal symptoms have been described in neonates following late pregnancy exposure to antipsychotic medication (Gentile, 2010;Habermann et al, 2013;Sadowski et al, 2013 effects-or-withdrawal-symptoms-in-newborns) have issued relevant safety labelling, and recommended relevant monitoring for neonates. However, studies that adequately controlled for confounding did not find a specific association between antipsychotic exposure and poor neonatal adaptation (Petersen et al, 2016;Vigod et al, 2015).…”
Section: Neonatal and Developmental Problemsmentioning
confidence: 99%
“…In general, studies that compare women exposed to antipsychotics in pregnancy to healthy unexposed women report moderately increased risks for several adverse maternal and infant outcomes (including congenital malformations, pre-term birth, fetal growth abnormalities and poor neonatal adaptation) (Boden et al, 2012b;Habermann et al, 2013;Reis and Kallen, 2008;Sadowski et al, 2013). By contrast, the few studies that used a comparison group of women with psychiatric illness but unexposed to antipsychotics (Boden et al, 2012a;Lin et al, 2010; National Institute for Health and Care Excellence, 2015a; Petersen et al, 2016), or studies that adequately controlled for confounding (Vigod et al, 2015), report few associations between antipsychotics and adverse maternal or infant outcomes.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…Other research on antipsychotic treatment in pregnancy includes pharmacovigilance studies from drug companies' safety databases 76,77 as well as cohort studies based on various data sources. 38,50,[78][79][80][81][82][83][84][85] A systematic review 19 of many of these studies suggested that women requiring antipsychotic treatment during pregnancy have a higher risk of adverse birth outcomes. However, there was substantial heterogeneity between the studies and Coughlin et al 19 emphasise that most studies had limited adjustment for potential confounding and therefore the observed associations may not be causal.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…Studies have suggested that antipsychotics are not or only slightly associated with increased risk of congenital malformations. [71][72][73][74][75][76] At the present time, it is difficult to define a clear connection between the development of malformations and the use of antipsychotics due to the lack of meta-analyses, systematic reviews, and adequate numbers of well-designed studies. Nevertheless, there are growing concerns on this issue.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…When compared with healthy women, the risk was 1.5-2.5 times higher. [72][73][74]77 Overall, first generation antipsychotics (FGAs) and second generation antipsychotics (SGAs) have similar prevalence rates with regard to congenital malformations. 72,73 A prospective cohort study with a large sample size suggested that the increased risk of specific organ malformations was related solely to the cardiovascular system.…”
Section: Congenital Malformationsmentioning
confidence: 99%